2019
DOI: 10.1177/0165551519861599
|View full text |Cite|
|
Sign up to set email alerts
|

Spam profiles detection on social networks using computational intelligence methods: The effect of the lingual context

Abstract: In online social networks, spam profiles represent one of the most serious security threats over the Internet; if they do not stop producing bad advertisements, they can be exploited by criminals for various purposes. This article addresses the nature and the characteristics of spam profiles in a social network like Twitter to improve spam detection, based on a number of publicly available language-independent features. In order to investigate the effectiveness of these features in spam detection, four dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Al-Zoubi et al 2019conducted experiments to compare the performance of NB, C4.5, SVM and KNN. Experimental results showed that SVM is the best classifier and gave the highest prediction accuracy of 96.99% (Al-Zoubi et al, 2019). Several researchers have explored this problem in past.…”
Section: Data Mining Based Methodsmentioning
confidence: 99%
“…Al-Zoubi et al 2019conducted experiments to compare the performance of NB, C4.5, SVM and KNN. Experimental results showed that SVM is the best classifier and gave the highest prediction accuracy of 96.99% (Al-Zoubi et al, 2019). Several researchers have explored this problem in past.…”
Section: Data Mining Based Methodsmentioning
confidence: 99%
“…The evaluation process of FS is accomplished based on the characteristics of the dataset (e.g., filters) or based on a learning algorithm (e.g., wrappers). Filters are fast methods because they do not involve a learning process [36,37]. However, wrappers generate more accurate results because the classifier used in the learning process of FS is normally used for the evaluation in the external testing process [30].…”
Section: Feature Selectionmentioning
confidence: 99%
“…The first data contained 3050 instances, while the second data contained 2200 instances. Furthermore, the preparation phase of the two data was done by applying several steps, including cleaning, labeling, remove stop words, normalization, and stemming [55,56].…”
Section: Data Description Collection and Preparationmentioning
confidence: 99%